Permanent Pacemaker Lead Induced Severe Tricuspid Regurgitation in Patient Undergoing Multiple Valve Surgery - Lee, Jung Hee (Korean J Thorac Cardiovasc Surg, 2015)
Severe and permanent tricuspid regurgitation induced by pacemaker leads is rarely reported in the literature. The mechanism of pacemaker-induced tricuspid regurgitation has been identified, but its management has not been well established. Furthermore, debate still exists regarding the proper surgical approach. We present the case of a patient with severe tricuspid regurgitation induced by a pacemaker lead, accompanied by triple valve disease. The patient underwent double valve replacement and tricuspid valve repair without removal of the pre-existing pacemaker lead. The operation was successful and the surgical procedure is discussed in detail.